Lack of association of post-discharge prophylactic antibiotics with decreased risk of surgical site infection following spinal fusion. (17th January 2022) - Olsen, Margaret A.; Greenberg, Jacob K.; Peacock, Kate; Nickel, Katelin B.; Fraser, Victoria J.; Warren, David K.
Abstract: Objectives: To determine the prevalence and factors associated with post-discharge prophylactic antibiotic use after spinal fusion and whether use was associated with decreased risk of surgical site infection (SSI). Methods: Persons aged 10–64 years undergoing spinal fusion between 1 January 2010 and 30 June 2015 were identified in the MarketScan Commercial Database. Complicated patients and those coded for infection from 30 days before to 2 days after the surgical admission were excluded. Outpatient oral antibiotics were identified within 2 days of surgical discharge. SSI was defined using ICD-9-CM diagnosis codes within 90 days of surgery. Generalized linear models were used to determine factors associated with post-discharge prophylactic antibiotic use and with SSI. Results: The cohort included 156 446 fusion procedures, with post-discharge prophylactic antibiotics used in 9223 (5.9%) surgeries. SSIs occurred after 2557 (1.6%) procedures. Factors significantly associated with post-discharge prophylactic antibiotics included history of lymphoma, diabetes, 3–7 versus 1–2 vertebral levels fused, and non-infectious postoperative complications. In multivariable analysis, post-discharge prophylactic antibiotic use was not associated with SSI risk after spinal fusion (relative risk 0.98; 95% CI 0.84–1.14). Conclusions: Post-discharge prophylactic oral antibiotics after spinal fusion were used more commonly in patients with major medical comorbidities, more complex surgeries and those with postoperative complications during the surgical admission. After adjusting for surgical complexity and infection risk factors, post-discharge prophylactic antibiotic use was not associated with decreased SSI risk. These results suggest that prolonged prophylactic antibiotic use should be avoided after spine surgery, given the lack of benefit and potential for harm.